Asian Anthropology - Van Bremen, jan; Ben-Ari, Eyal; Farid Alatas, Syed (Anthropology of Asia, 2005)
Asian Anthropology raises important questions regarding the nature of anthropology and particularly the production and consumption of anthropological knowledge in Asia. Instead of assuming a universal standard or trajectory for the development of anthropology in Asia, the contributors to this volume begin with the appropriate premise that anthropologies in different Asian countries have developed and continue to develop according to their own internal dynamics. With chapters written by an international group of experts in the field, Asian Anthropology will be a useful teaching tool and a valuable resource for scholars working in Asian anthropology.